2021
DOI: 10.3390/membranes11060425
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of a (Vinylbenzyl) Trimethylammonium and N-Vinylimidazole-Substituted Poly (Vinylidene Fluoride-Co-Hexafluoropropylene) Copolymer as an Anion-Exchange Membrane in a Lignin-Oxidising Electrolyser

Abstract: Electrolysis is seen as a promising route for the production of hydrogen from water, as part of a move to a wider “hydrogen economy”. The electro-oxidation of renewable feedstocks offers an alternative anode couple to the (high-overpotential) electrochemical oxygen evolution reaction for developing low-voltage electrolysers. Meanwhile, the exploration of new membrane materials is also important in order to try and reduce the capital costs of electrolysers. In this work, we synthesise and characterise a previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…The finite supply of fossil fuels and environmental pollution are major concerns for global climate and have accelerated the implementation of alternative energy technologies without any emission of greenhouse gases. 1 Effective utilization of renewable energy (solar, wind, etc.) has great potential in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…The finite supply of fossil fuels and environmental pollution are major concerns for global climate and have accelerated the implementation of alternative energy technologies without any emission of greenhouse gases. 1 Effective utilization of renewable energy (solar, wind, etc.) has great potential in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…6). The most common relevant backbones cited in the literature used for AEMs are: polysulphone type [262][263][264][265][266] poly(ether ketone) type, [267][268][269][270] poly(ether imide) type, [271][272][273] poly(ether oxadiazole) type, [275][276][277] and poly(phenylene oxide) type, 274,[278][279][280][281][282] polyphenylene type, [283][284][285] fluorinated type, [286][287][288][289][290][291] polybenzimidazole type, [292][293][294][295][296][297][298] polyethylene type, [299][300][301][302][303][304][305][306] and polystyrene type. 264,…”
Section: Alkaline Water Electrolysermentioning
confidence: 99%
“…Recently, various ratios (4-10%) of (vinylbenzyl)trimethylammonium chloride were functionalized with the uorinated polymer (PVIB), revealing the increase in the IEC (1.43-1.82 mmol g −1 ). 326 Increasing the number of (vinylbenzyl)trimethylammonium chloride in the membrane could enhance the ion exchanges between the polymer backbone and QAs. Another research found that the IECs decreased from 2.84 to 1.55 mmol g −1 when the amount of extended alkyl chain-based bis-piperidinium cation groups in the quaternized membrane (e.g., QPBPip-Ac) was increased (from 33% to 67%).…”
Section: Iec ¼ ðVmentioning
confidence: 99%